Financial Reforms in Sudan : Streamlining Bank Intermediation - Kireyev, Alexei (IMF Working Papers; Working Paper, 2001)
The paper reviews the experience of financial reforms in Sudan with a view to assessing their macroeconomic impact and to shedding light on the question why such reforms have not yet brought about visible improvements in financial intermediation. The paper concludes that regardless of the progress achieved in recent years, deficiencies in the reform design, institutional weaknesses, shallow financial markets, shortcomings of the Islamic mode of finance, and strong seasonality remain key factors that constrain financial intermediation. Additional efforts, in particular in bank restructuring, credit instrument design, monetary policy management, and prudential regulation are needed to address the systemic problems of the financial sector and to make it capable of supporting private sector growth.